IMPLEMENTASI MEDIA KOMIK MATEMATIKA DIGITAL DALAM PEMBELAJARAN POLA BARISAN BILANGAN [USING DIGITAL MATHEMATICS COMICS TO TEACH NUMBER SEQUENCE PATTERNS] - Suwito, Ruth Widyati; Sa'dijah, Cholis; Qohar, Abd. (Universitas Pelita Harapan, 2023)
One of the problems with learning mathematics is students' difficulty in understanding the material. This difficulty is often accompanied by a sense of boredom, especially at the junior high school level. One solution to address this issue is the use of self-designed and organized digital mathematics comics to help students overcome difficulties and capture their attention. This research aims to implement valid and practical digital mathematics comics in the learning of number sequence pattern. This qualitative descriptive research was conducted by collecting data through questionnaires, observation sheets, and unstructured interviews. In the implementation of learning number sequence patterns using digital mathematics comics, 88 percent were found to be valid, and 89 percent were proven to be very practical based on the responses of 9 eighth-grade students from one of the private junior high schools in Malang who used it. Students were able to read, interact actively, and complete each exercise available in the media. Teaching mathematics using digital mathematics comics is recommended for implementation in other schools.BAHASA INDONESIA ABSTRACT: Salah satu masalah yang terjadi pada pembelajaran matematika adalah kesulitan siswa dalam memahami materi. Kesulitan yang biasanya disertai oleh rasa bosan dialami oleh siswa terlebih pada jenjang SMP. Salah satu solusi untuk menjawab permasalahan tersebut adalah penggunaan media komik matematika digital yang didesain dan disusun sendiri untuk membantu siswa mengatasi kesulitan dan menarik perhatian siswa. Penelitian ini dilakukan untuk menganalisis implementasi media komik matematika digital yang valid dan praktis dalam pembelajaran pola barisan bilangan. Penelitian dengan metode deskriptif kualitatif ini dilakukan dengan cara mengumpulan data melalui angket, lembar pengamatan, dan wawancara tidak terstruktur. Pada implementasi pembelajaran pola barisan bilangan dengan media komik matematika digital yang 88 persen sudah valid, terbukti 89 persen sangat praktis berdasarkan respons 9 siswa kelas 8 di salah satu SMP Swasta Malang yang telah menggunakannya. Siswa dapat membaca, berinteraksi dengan aktif, dan mengerjakan setiap latihan soal yang sudah tersedia pada media tersebut. Pembelajaran matematika dengan menggunakan komik matematika digital ini direkomendasikan untuk dapat diimplementasikan di sekolah-sekolah lain.